Design and comparison of dual‐stator axial‐field flux‐switching permanent magnet motors for electric vehicle application - Fariba Farrokh; Abolfazl Vahedi; Hossein Torkaman; Mahdi Banejad (IET Electrical Systems in Transportation)
Abstract In this article, three dual‐stator axial field flux‐switching permanent magnet (DS‐AFFSPM) topologies are selected, designed, and analysed in order to determine the most effective structure electric vehicle (EV) application based on torque density, power density, and efficiency. Accordingly, the introduced topologies are thoroughly compared in the same condition. The results show that, the high‐power density, high‐torque density, and high‐efficiency, of the internal single‐teeth rotor DS‐AFFSPM topology is a suitable candidate for EV application because it has the lowest torque ripple.